Education On How To Wash Hands Properly And Correctly Using Soap During the Covid-19 Pandemic To The Village Community - Herda Ariyani (UMBanjarmasin, 2021)
The purpose of this service is to provide education in providing knowledge to residents in Sungai Pitung Village Barito Kuala South Kalimantan Indonesia about proper and proper hand washing and the use of soap during Covid-19. The target of this service is residents in this Village. This service was attended by 18 children of various ages. This method of dedication uses direct methods such as lectures and questions and answers. The instruments of this service are tables, pictures, and questionnaire sheets of the pre-test and post-test as well as hand washing soap. The results of this service, on the pre test, show that the majority of residents of this Village already know the importance of washing their hands. However, they still do not understand the steps for washing hands and when to wash their hands. Then, based on the results of the post test given it proved that there was a significant increase. The public became more aware after listening to the education that was conveyed about washing hands as a prevention of disease and to break the chain of spreading Covid-19. In addition, people become more aware of when to wash their hands, the benefits of washing hands, the consequences of not washing their hands, and the characteristics of good hand washing soap, as well as how to wash their hands properly and correctly with soap during the Covid-19 pandemic.